Artificial intelligence in healthcare: A focus on the best practices - Haddiya Intissar; Ramdani Sara (ITM Web of Conferences)
The healthcare sector is undergoing a significant transformation driven by Artificial Intelligence (AI). AI applications in clinical practice offer a multitude of benefits for patient care, including earlier and more accurate diagnoses, personalized treatment planning, and improved access to information through virtual assistants. However, alongside this potential, challenges and ethical considerations remain. Data privacy, algorithmic bias, transparency of AI decision-making, and responsible use are crucial areas that require careful attention. Our presentation emphasizes the importance of establishing robust best practices within healthcare institutions and fostering collaboration among clinicians, data scientists, patients, and policymakers. Through careful consideration and ongoing refinement of AI technologies, we can leverage its potential to improve patient outcomes while upholding ethical standards and public health priorities.